Coupling of phagocytic NADPH oxidase activity and mitochondrial superoxide production - Dikalov, Sergey I.; Dikalova, Anna E.; Kirilyuk, Igor A. (Frontiers in Cardiovascular Medicine, 2022)
Superoxide radical plays an important role in cell signaling and physiological processes; however, overproduction of superoxide or insufficient activity of antioxidants leads to oxidative stress and contributes to the development of pathological conditions such as endothelial dysfunction and hypertension. The studies of superoxide in biological systems represent unique challenges associated with short lifetime of superoxide, insufficient reactivity of the superoxide probes, and lack of site-specific detection of superoxide. In this work we have developed 15N-and deuterium-enriched spin probe 15N-CAT1H for high sensitivity and site-specific detection of extracellular superoxide. We have tested simultaneous tracking of extracellular superoxide by 15N-CAT1H and intramitochondrial superoxide by conventional 14N-containing spin probe mitoTEMPO-H in immune cells isolated from spleen, splenocytes, under basal conditions or stimulated with inflammatory cytokines IL-17A and TNF, NADPH oxidase activator PMA, or treated with inhibitors of mitochondrial complex I rotenone or complex III antimycin A. 15N-CAT1H provides two-fold increase in sensitivity and improves detection since EPR spectrum of 15N-CAT1 nitroxide does not overlap with biological radicals. Furthermore, concurrent use of cell impermeable 15N-CAT1H and mitochondria-targeted 14N-mitoTEMPO-H allows simultaneous detection of extracellular and mitochondrial superoxide. Analysis of IL-17A- and TNF-induced superoxide showed parallel increase in 15N-CAT1 and 14N-mitoTEMPO signals suggesting coupling between phagocytic NADPH oxidase and mitochondria. Tnterplay between mitochondrial superoxide and activity of phagocytic NADPH oxidase was further investigated in splenocytes isolated from Sham and angiotensin II infused C57Bl/6J and Nox2KO mice. Angiotensin II infusion in wild-type mice increased the extracellular basal splenocyte superoxide which was further enhanced by complex III inhibitor antimycin A, mitochondrial uncoupling agent CCCP and NADPH oxidase activator PMA. Nox2 depletion attenuated angiotensin II mediated stimulation and inhibited both extracellular and mitochondrial PMA-induced superoxide. These data indicate that splenocytes isolated from hypertensive angiotensin II-infused mice are “primed” for enhanced superoxide production from both phagocytic NADPH oxidase and mitochondria. Our data demonstrate that novel 15N-CAT1H provides high sensitivity superoxide measurements and combination with mitoTEMPO-H allows independent and simultaneous detection of extracellular and mitochondrial superoxide. We suggest that this new approach can be used to study the site-specific superoxide and analysis of important sources of oxidative stress in cardiovascular conditions.